If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 = 6q + -16 Reorder the terms: 14 = -16 + 6q Solving 14 = -16 + 6q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-6q' to each side of the equation. 14 + -6q = -16 + 6q + -6q Combine like terms: 6q + -6q = 0 14 + -6q = -16 + 0 14 + -6q = -16 Add '-14' to each side of the equation. 14 + -14 + -6q = -16 + -14 Combine like terms: 14 + -14 = 0 0 + -6q = -16 + -14 -6q = -16 + -14 Combine like terms: -16 + -14 = -30 -6q = -30 Divide each side by '-6'. q = 5 Simplifying q = 5
| 10-3n=4 | | 15=c+-12 | | 18+2p=4 | | 4x+30=x+12 | | (27a^3b^9)^2/3 | | 15-4y=3 | | x^2-(4/25)=0 | | 10(7x-5)=300 | | x^2-0.16=0 | | 125-2x=16x+19 | | 13-7x=9x+17 | | 10+8=6x+36 | | 2k^2+26k-13=0 | | F(2)=12*2-6 | | 3x+12-x=18 | | 16*11+7x*16=2640 | | 16*11+7x=2640 | | 19x-162=9 | | 9(20x-19)=2169 | | 3*4x-3*3=12x-2 | | 14(6+17x)=3654 | | 15x-38=7 | | 22x-410=8 | | 10*4x-3*10=38-6 | | 4x^2-10x-1=0 | | 19*5-8x*19=-2185 | | 17x-222=16 | | 17x=323 | | 15(5-14x)=-2655 | | 11*9-8*9=97-2 | | 3*4+21x*6=1272 | | 16(17x-21)=2656 |